2015
DOI: 10.1177/0018726715575359
|View full text |Cite
|
Sign up to set email alerts
|

Pay dispersion and organizational innovation: The mediation effects of employee participation and voluntary turnover

Abstract: Building on social comparison theory, we posit that a firm’s pay dispersion affects its innovation through employee participation and voluntary turnover. By analyzing data collected at both employee and organizational levels from 1419 firms, we found that pay dispersion had an inverted U-shaped effect on employee participation, which in turn enhanced innovation. Pay dispersion had a positive effect on voluntary turnover, which in turn impaired innovation. These findings contribute to research on economic inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 71 publications
0
48
0
1
Order By: Relevance
“…Direct voice mechanism is a “direct” participation arrangement that provides opportunities to make suggestions (Wang et al, ). It broadens the avenue through which employees can actively express concerns, complaints, opinions, and views that emerge at work to management across the company.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Direct voice mechanism is a “direct” participation arrangement that provides opportunities to make suggestions (Wang et al, ). It broadens the avenue through which employees can actively express concerns, complaints, opinions, and views that emerge at work to management across the company.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Some researchers (Kimhi, 2010;Rapoport, 2002) have suggested that motivations for increased income may motivate entrepreneurship in developing countries as well. At the organizational level, Wang, Zhao, and Thornhill (2015) drawing from social comparison theory show that up to a certain level pay differences motivate corporate entrepreneurship/innovation as employees are more likely to increase their level of organizational engagement to improve their opportunities to increase their pay. This supports arguments that it is often the hope of achieving great wealth that makes would-be entrepreneurs more willing to pursue risky ventures (Lippmann et al, 2005).…”
Section: Income Inequality and Eamentioning
confidence: 99%
“…Theories such as relative deprivation theory (Crosby 1976) and equity theory (Adams 1963(Adams , 1965 indicate that whether employees perceive their pay as being fair depends on their pay compared to the pay of referent others (e.g., colleagues or employees in other organizations). Several studies have shown that employees' pay relative to referents is associated with work-related attitudes, such as pay equity perceptions (e.g., Trevor and Wazeter 2006), perceived pay fairness (e.g., Shore et al 2006), and pay satisfaction (e.g., Williams et al 2006), and behaviors, such as absenteeism (see, e.g., Della Torre et al 2015) and turnover (see, e.g., Wade et al 2006;Wang et al 2015).…”
Section: Theoretical Background and Hypotheses Pay And Job Performancementioning
confidence: 99%
“…Researchers have distinguished between internal pay disparities, which are defined as differences in employee pay within an organization, and external pay disparities, which refer to pay differentials between organizations. Studies have shown that employees' pay relative to colleagues (i.e., internal pay standing) and their salary relative to employees in other organizations who perform similar tasks (i.e., external pay standing) are related to employee behavior and attitudes, such as pay satisfaction (see, e.g., Harris et al 2008;Williams et al 2006), absenteeism (see, e.g., Della Torre et al 2015, and turnover (see, e.g., Wade et al 2006;Wang et al 2015). These studies have contributed to our understanding of how employees react to pay disparities.…”
Section: Introductionmentioning
confidence: 99%